TINJAUAN HUKUM PRAKTIK BISNIS BERKEADILAN MELALUI PENINGKATAN AKSESIBILITAS KONSUMEN - Harahap, Abi Jumroh (Universitas Muhammadiyah Sumatera Utara, 2017)
In the mid of free trade era, both in domestic and international level, consumer protection issues has become more relevan to be examined. One of the important aspect in the field of consumer protection that should be strengthened is consumer’s access to justice. The complexity of global trade marked by unfair commercial practices have often negative impacts for consumer; consumer rights often be ignored and violated by business people. Therefore government must be able to ensure the existence of consumer’s access to justice through the rule making, policy, and the new legal institutionalization in order to create fair business environment.